Ten Rules for the Management of Moderate and Severe Traumatic Brain Injury During Pregnancy: An Expert Viewpoint - Di Filippo, Simone; Godoy, Daniel Agustin; Manca, Marina; Paolessi, Camilla; Bilotta, Federico; Meseguer, Ainhoa; Severgnini, Paolo; Pelosi, Paolo; Badenes, Rafael; Robba, Chiara (Frontiers in Neurology, 2022)
Moderate and severe traumatic brain injury (TBI) are major causes of disability and death. In addition, when TBI occurs during pregnancy, it can lead to miscarriage, premature birth, and maternal/fetal death, engendering clinical and ethical issues. Several recommendations have been proposed for the management of TBI patients; however, none of these have been specifically applied to pregnant women, which often have been excluded from major trials. Therefore, at present, evidence on TBI management in pregnant women is limited and mostly based on clinical experience. The aim of this manuscript is to provide the clinicians with practical suggestions, based on 10 rules, for the management of moderate to severe TBI during pregnancy. In particular, we firstly describe the pathophysiological changes occurring during pregnancy; then we explore the main strategies for the diagnosis of TBI taking in consideration the risks related to mother and fetus, and finally we discuss the most appropriate approaches for the management in this particular condition. Based on the available evidence, we suggest a stepwise approach consisting of different tiers of treatment and we describe the specific risks according to the severity of the neurological and systemic conditions of both fetus and mother in relation to each trimester of pregnancy. The innovative feature of this approach is the fact that it focuses on the vulnerability and specificity of this population, without forgetting the current knowledge on adult non-pregnant patients, which has to be applied to improve the quality of the care process.